VALUE CHAIN ANALYSIS OF CASSAVA AND CASSAVA BYE PRODUCTS IN OGUN STATE NIGERIA: A TRANSLOG COST FUNCTION APPROACH (FUDMA JOURNAL OF SCIENCES, 2023)
In this article, value chain analysis of cassava and cassava bye product in Ogun state Nigeria: a translog cost function approach is examined. A Multistage sampling technique was used to select 180 cassava processors and marketers. Socio-economic and household data were obtained from respondents with the use of pre-tested questionnaires. Data were analysed using descriptive statistics, budgetary technique, Translog Cost Function and Student t-test. The study found that majority (84.3% and 52.8%) of processors of cassava peels and marketers were female. In addition, 60.2% of the processors and 51.4% of the marketers had secondary education respectively. The value chain activities carried out by processors were transportation, drying and packaging while marketers transported, packaged and store peels for future sales. The Translog Cost Function Approach revealed that for cassava peel quantity processing, coefficient of labour equation is positive and significant at 5%. The positive sign of the coefficient implies that the share of wage rate of labour increases with increase in the cassava peel processing in the study area. This has put cassava peel at vintage position in terms of labour use and other expenses along the cassava value chain when compared to the other cassava products. The study recommends considering the share of revenue generated from the cassava products and by-products, in terms of wage rate and prices of other inputs, larger share of the revenue should be direct to cassava peel in order to maximize profit generated from this product. Also, based on economies of scale, cassava processors
Keywords: cassava product, bye product, value chain, marketers, processors